Meteorological and soil data from Bayelva, Svalbard, homogenised data product (version 2: 1998-09-13 to 2024-12-31, design 2: one row per time-step) - Grünberg, Inge; Miesner, Frederieke; Bornemann, Niko; Cable, William L; Boike, Julia (In: Grünberg, I et al. (2024): Meteorological and soil data from Bayelva, Svalbard, homogenised data product (1998 et seq.) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.969343, 2025)
Understanding permafrost processes and their links to polar climate requires long-term observational datasets. This data product is a quality-controlled and homogenised selection of meteorological and soil data from the Bayelva long-term observatory near Ny-Ålesund, Svalbard, which has been in operation since 1998. We combined the data from multiple sensors at the site into a single, consistent dataset with hourly resolution and corrected for known offsets of specific sensors. The data provide observations of temporally variable parameters that mitigate energy fluxes between the soil and atmosphere, such as snow depth, liquid precipitation, air temperature, relative humidity, wind speed and direction, and radiation fluxes. Furthermore, the data cover active layer and permafrost temperature and moisture at multiple depths. The quality-controlled and homogenised data product is suitable for use in integrating, calibrating, and testing permafrost as a component in Earth System Models. A dataset of this length and completeness is unique in the Arctic and serves as a baseline for future studies. The data are provided in two designs: Design (1) is oriented vertically with multiple rows per time stamp covering the different observation heights and depths. Empty rows are excluded. This design is most suitable for applications which require machine readable data. Design (2) is oriented horizontally with a single row per time stamp and multiple columns for soil temperature and moisture at different depths. It includes data gaps as empty rows. This design is human readable and most suitable for integration in custom programmed code. The datasets in both designs include the same values. This data product is a homogenised compilation of data from different sensors at the Bayelva long-term observatory published in annual files in the two collections listed in 'Comment'. While the original data includes half-hourly measurements of climate and soil data with raw values and quality flags, this product includes only high quality data at hourly resolution.
Keywords: active layer; air temperature; Arctic; Bayelva; longwave radiation; Ny-Ålesund; Permafrost; precipitation; relative humidity; shortwave radiation; snow depth; snow height; Soil; Soil Moisture; soil temperature; Svalbard; volumetric water content; wind direction; wind speed